2020
DOI: 10.30605/25409190.219
|View full text |Cite
|
Sign up to set email alerts
|

English as Medium of Instruction Implementation for Communication and Sustainability in 4.0 Era

Abstract: Globalization spreads fast around the world put English language become a-must-have skill. Almost all people use English in the teaching learning process, communication, transferring soft skills and hard skills, showing social status in communities, business transactions, political purposes, even on the some medicine instruction, food ingredients, mechanic usage instruction, and many more. The language is used to various purposes, as for online and offline communication. During this corona virus pandemic, Engl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The results indicated that the ‘bilingual instruction approach’ was much preferred by students, and the researchers concluded that ‘one of the reasons is due to students’ limited proficiency’ as the ‘[l]ow level of English proficiency to some extent inhibits or impedes students’ ability to understand and comprehend teachers’ explanation in English’ (p. 208). Sela and Luke (2020) investigated EMI instruction delivered by 52 lecturers and 52 students at the private BINUS university in Jakarta. The research questions they asked were (i) How essential is English for communication in the 4.0 era?…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results indicated that the ‘bilingual instruction approach’ was much preferred by students, and the researchers concluded that ‘one of the reasons is due to students’ limited proficiency’ as the ‘[l]ow level of English proficiency to some extent inhibits or impedes students’ ability to understand and comprehend teachers’ explanation in English’ (p. 208). Sela and Luke (2020) investigated EMI instruction delivered by 52 lecturers and 52 students at the private BINUS university in Jakarta. The research questions they asked were (i) How essential is English for communication in the 4.0 era?…”
Section: Literature Reviewmentioning
confidence: 99%
“…Task-based approach embodies humanism and solves the contradiction between meaning and form of language in theory. Task-based approach emphasizes interaction and communication through the use of the target language and introduces the real context into learning ( Sela and Luke, 2020 ). To provide learners with the opportunity to master the learning process, in the process of learning by enhancing the experience of learners to improve the enthusiasm of learning, task-based approach combines classroom language with extracurricular language to improve learners’ language use ability and thinking ability.…”
Section: Content-based Instruction Teaching Concept and College Engli...mentioning
confidence: 99%
“…The EMI is not implemented purely instead it tends to be a bilingual class. Sela, & Luke, (2020) argued that adopting EMI is essential for sustaining communication in the present era although the implementation of EMI is not always run smoothly due to some drawbacks that could not be avoided by the lecturer, learners and educators need to build awareness to its usage as well as make adjustment in conducting it fully in the classroom. One best thing to do is to incorporate the implementation of EMI with the use of technology in the teaching and learning process.…”
Section: Literature Review Emi In Global Linguistic Contextmentioning
confidence: 99%